A Study Of English Code-Switching In Indonesian Teen Magazine - Ria Saraswati; Rr.Astri Indriana Octavita (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2016)
This study explores some important issues, namely the occurrences of code switching types, and function in teen magazines articles. Some theories were used to analyse the data, namely Poplack (1980) was used to identify types of code switching and Koziol (2000) was applied to investigate functions of Code Switching. Based on the results of analysis, it shows that there were three types of code switching found in teen magazine articles e.g. Intrasentential Switching, Intersentential Switching, and Tag Switching. In term of functions of code switching, nine functions were identified namely personalization, reiteration, designation, emphasis, calrification, untranslatability, mitigating message, interjection parenthesis, aggravating message, and topic shift.The findings reveal intra-sentential switching as the type which dominates the discourse in the magazine (62.50 %). Meanwhile, emphasis function is the most frequent function occurs in the magazine (45.39 %).Keywords: teen magazine, code switching types, code switching functions